2017
DOI: 10.1007/s10071-017-1137-z
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous integration of temporal information: implications for representational/computational capacity of animals

Abstract: How do animals adapt their behaviors to changing conditions? This question relates to the debate between associative versus representational/computational approaches in cognitive science. An influential line of research that has significantly shaped the conceptual development of animal learning over decades has primarily focused on the role of associative dynamics with little-to-no ascription of representational/combinatorial capacities. The common assumption of these models is that behavioral adjustments are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 102 publications
0
8
4
Order By: Relevance
“…Some subjects do show something that could be described as an abrupt acquisition, but response variability is too large throughout the experiment to make this conclusion meaningful when, to put it simply, a sharp initial rise in response is yet another random fluctuation around the ideal average curve (see Figures S4, S6). Precisely for the same reason, although it is true that traditional associative models do not predict abrupt chances in behavior, our findings do not support representational or model-based models either (Gür et al, 2018). Response variability is so fine grained that its random, nowheredifferentiable nature is, in our opinion, unquestionable.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Some subjects do show something that could be described as an abrupt acquisition, but response variability is too large throughout the experiment to make this conclusion meaningful when, to put it simply, a sharp initial rise in response is yet another random fluctuation around the ideal average curve (see Figures S4, S6). Precisely for the same reason, although it is true that traditional associative models do not predict abrupt chances in behavior, our findings do not support representational or model-based models either (Gür et al, 2018). Response variability is so fine grained that its random, nowheredifferentiable nature is, in our opinion, unquestionable.…”
Section: Discussioncontrasting
confidence: 75%
“…• The main average effects of overtraining are an extremely slow decrease of the post-CS response and a fast extinction (see Figure S10). Fast extinction points out that the response of the animals during the experiment was not driven by habit, contrary to what one might expect in long training histories (Gür et al, 2018).…”
Section: Discussioncontrasting
confidence: 58%
“…Subjects in associative learning experiments make a temporal map of the conditioning experience (Balsam & Gallistel, 2009;Honig, 1981;Taylora, Joseph, Zhaoc, & Balsam, 2014). The temporal information in the map affects every aspect of Pavlovian and operantly conditioned behavior (Arcediano & Miller, 2002;Barnet, Grahame, & Miller, 1993;Barnet & Miller, 1996;Blaisdell, Denniston, & Miller, 1998;Burger, Denniston, & Miller, 2001;Cole, Barnet, & Miller, 1995;Cunningham & Shahan, 2018;Denniston, Blaisdell, & Miller, 1998, 2004Gallistel, Craig, & Shahan, 2019;Gür, Duyan, & Balci, 2017;Shahan & Cunningham, 2015;Theunissen & Miller, 1995;Thrailkill & Shahan, 2014).…”
Section: Time In Conditioningmentioning
confidence: 99%
“…Subjects appear to do computations with the wait times they have learned (Gür et al, 2017): For example, the rate of learning [1/(trials to acquisition)] is a scalar function of the C/T ratio, which, as already noted, is the ratio of the basal average wait time for reinforcement in the training context (C) and the average wait time (T) for reinforcement following the onset of the conditioned stimulus (CS for short). The larger the C/T ratio is, the fewer the number of reinforced trials required for the appearance of a conditioned response to the CS (Gallistel & Gibbon, 2000;Gibbon & Balsam, 1981;Gottlieb, 2008;Jenkins, Barnes, & Barrera, 1981;Sunsay & Bouton, 2008).…”
Section: Time In Conditioningmentioning
confidence: 99%
“…Our earlier work has shown that humans and mice can integrate probability information into their temporal decisions in an adaptive fashion (e.g., maximizing reward-rate; Balci et al, 2009b; Kheifets and Gallistel, 2012; Çoskun et al, 2015; Akdoğan and Balcı, 2016) and they can do this abruptly and spontaneously (Tosun et al, 2016; for a review, see Gür et al, 2018). Regarding these functional endpoints, earlier studies show that sensitivity to probabilistic information is higher in young compared to elderly (Howard et al, 2008), which becomes more pronounced with extended practice (Simon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%